Corneal Cross-Linking for Keratoconus: Current Knowledge and Practice and Future Trends. Issue 6 (November 2020) - Chan, Colin
Abstract : Abstract: Corneal collagen cross-linking (CXL) with riboflavin is an accepted universal standard of care for our keratoconus patients with progressive disease. It has been a game changer in how we manage keratoconus. Early diagnosis and treatment is essential in paediatric patients as younger patients progress more rapidly and have poorer transplant outcomes. There is an ongoing debate around standard, accelerated, and transepithelial protocols of CXL, the role of CXL, and the combination of laser refractive surgery. Future developments will improve CXL safety and efficacy and the scope of utilization, but we must be careful not to leap too far ahead with clinical applications before publication of basic science research and good clinical results with standardized protocols.